2021
DOI: 10.1177/00027642211042284
|View full text |Cite
|
Sign up to set email alerts
|

Groupies, Fangirls and Shippers: The Endurance of a Gender Stereotype

Abstract: The purpose of this special issue is to offer new perspectives on fan cultures which respond to changes and controversies that have happened since the last American Behavioral Scientist special issue on fandom was published, in 2005. But the aim of my contribution is to argue that, sadly, derisive-gendered discourses like ‘fangirls’, ‘groupies’ and ‘shippers’ are still alive and well. Returning to the kind of research conducted in the 1980s – when women’s experiences of feminized popular cultures began to be t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…On the other hand, it might offer insights into how fans deal with stereotypes of being a female fan at a later age. Interestingly, studies have shown that the 'gender stereotype' endures and is even held in place by 'older' female fans towards younger female fans (Gerrard 2022). Referring to and deriding the younger women as 'fangirls', helps to create and establish a feeling of legitimacy for their own position as older fans, but also to make a distinction that the demographic targeted are the younger fans (Gerrard 2022).…”
Section: Post-youth Fans and Life-long Pop Fandommentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it might offer insights into how fans deal with stereotypes of being a female fan at a later age. Interestingly, studies have shown that the 'gender stereotype' endures and is even held in place by 'older' female fans towards younger female fans (Gerrard 2022). Referring to and deriding the younger women as 'fangirls', helps to create and establish a feeling of legitimacy for their own position as older fans, but also to make a distinction that the demographic targeted are the younger fans (Gerrard 2022).…”
Section: Post-youth Fans and Life-long Pop Fandommentioning
confidence: 99%
“…Interestingly, studies have shown that the 'gender stereotype' endures and is even held in place by 'older' female fans towards younger female fans (Gerrard 2022). Referring to and deriding the younger women as 'fangirls', helps to create and establish a feeling of legitimacy for their own position as older fans, but also to make a distinction that the demographic targeted are the younger fans (Gerrard 2022). In Gerrard's study (2022) there seems to be a sense of ageism going on: framing the younger fans as controversial and doing so to generate a form of pleasure which leads to the older fan being an 'educator' of younger fans.…”
Section: Post-youth Fans and Life-long Pop Fandommentioning
confidence: 99%
See 2 more Smart Citations
“…It can be in the form of romance, friendship, family, and emotion. They always connect the activities of each idol as if they have a relationship with one another (Gerrard, 2021) shipper used in this research is a Blackpink fan named Jenlisa Universe. Jenlisa Universe is a shipper community that pairs Blackpink members Jennie and Lisa in a relationship.…”
Section: Shippers and Fandomsmentioning
confidence: 99%